(untitled) (San Francisco, 2009)
Using the story/parable format so popular these days, Leadership and Self-Deception takes a novel psychological approach to leadership. It's not what you do that matters, say the authors (presumably plural--the book is credited to the esteemed Arbinger Institute), but why you do it. Latching onto the latest leadership trend won't make people follow you if your motives are selfish--people can smell a rat, even one that says it's trying to empower them. The tricky thing is, we don't know that our motivation is flawed. We deceive ourselves in subtle ways into thinking that we're doing the right thing for the right reason. We really do know what the right thing to do is, but this constant self-justification becomes such an ingrained habit that it's hard to break free of it--it's as though we're trapped in a box, the authors say.
Keywords: Leadership,Self-deception